(untitled) (Journal of Pharma Insights and Research, 2025)
Hepatic encephalopathy (HE) occurs as a spectrum of neuropsychiatric abnormalities in patients with compromised liver function. While ammonia has traditionally been considered the primary mediator in, HE pathogenesis, recent evidence indicates that inflammation plays a crucial role in disease progression. The liver’s impaired function leads to elevated blood ammonia levels, causing neurotoxic effects and contributing to cognitive dysfunction, lethargy, and potential progression to coma. However, clinical observations reveal that ammonia levels alone do not correlate perfectly with disease severity, suggesting the involvement of additional factors. Systemic inflammation and neuroinflammation are attributed as significant contributors to HE progression, working synergistically with ammonia to worsen cognitive impairment and accelerate disease progression. Current therapeutic regimens primarily focus on reducing blood ammonia levels, but these approaches often have notable side effects and may not address all aspects of the disease. Plant-based interventions, with their inherent anti-inflammatory properties, present a promising alternative therapeutic approach. Several plants and their bioactive compounds, including genistein, rutin, chrysin, allicin, and thymoquinone, have demonstrated significant potential in preclinical studies by modulating inflammatory pathways and improving cognitive function in HE models. These natural compounds may offer effective therapeutic options with potentially fewer side effects compared to conventional treatments. Integration of anti-inflammatory strategies, particularly plant-based interventions, into HE management protocols may enhance treatment outcomes and improve patient quality of life